PERHITUNGAN NILAI IRI MENGGUNAKAN MODEL IRRE DENGAN SIMULASI BERBAGAI VARIANSI KONDISI PERMUKAAN - Effendi Radia; R. Anwar Yamin; Kurniadji Kurniadji (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
Surface roughness is one of important parameters in road maintenance management, thus characterictics of that roughness is important to be understood. During the past time, the affect of road surface form and it's dimention againts road surface roughness so far is unknown well. This paper tries to know the affect of variation of road surface form and it's dimention toward road surface roughness expressed in term of IRI, by use of IRRE calculation model of IR.